Design of Briquette Printing Machine Using QFD for Coffee Waste Utilization - Adyatama, Achmad Reza; Caesaron, Dino; Mufidah, Ilma (School of Industrial and System Engineering, Telkom University, 2025)
The ever-increasing coffee production in West Java generates considerable coffee ground waste, especially from the coffee concentration process by Aroma Kahuripan. This waste has the potential to pollute the environment due to the presence of certain substances in it. This research aims to design a briquette printing machine to optimize the processing of coffee ground waste as part of the circular economic implementation. The research method used is the Quality Function Deployment (QFD) approach to identify user needs, followed by the process of concept development, concept selection, and prototyping. The designed machine uses a frame made of galvanized iron and is equipped with an electric-based drive system. The evaluation results show that this machine can process coffee ground waste into briquettes effectively with low noise levels and efficient maintenance time. This machine is expected to improve the sustainability of Aroma Kahuripan's production through more environmentally friendly waste management and support the concept of circular economy by utilizing waste into valuable products.